Nuclear genetic defects of mitochondrial ATP synthase - Hejzlarová, K; Mráček, T; Vrbacký, M; Kaplanová, V; Karbanová, V; Nůsková, H; Pecina, P; Houštěk, J (Physiological research, 2014)
Disorders of ATP synthase, the key enzyme of mitochondrial energy provision belong to the most severe metabolic diseases presenting as early-onset mitochondrial encephalo-cardiomyopathies. Up to now, mutations in four nuclear genes were associated with isolated deficiency of ATP synthase. Two of them, ATP5A1 and ATP5E encode enzyme's structural subunits alpha and epsilon, respectively, while the other two ATPAF2 and TMEM70 encode specific ancillary factors that facilitate the biogenesis of ATP synthase. All these defects share a similar biochemical phenotype with pronounced decrease in the content of fully assembled and functional ATP synthase complex. However, substantial differences can be found in their frequency, molecular mechanism of pathogenesis, clinical manifestation as well as the course of the disease progression. While for TMEM70 the number of reported patients as well as spectrum of the mutations is steadily increasing, mutations in ATP5A1, ATP5E and ATPAF2 genes are very rare. Apparently, TMEM70 gene is highly prone to mutagenesis and this type of a rare mitochondrial disease has a rather frequent incidence. Here we present overview of individual reported cases of nuclear mutations in ATP synthase and discuss, how their analysis can improve our understanding of the enzyme biogenesis.
Keywords: Mitochondria; modely genetické; jednonukleotidový polymorfismus; mutace; Models, Genetic; Polymorphism, Single Nucleotide; mitochondriální nemoci; Animals; Mitochondrial Diseases; Humans; Mutation; Mitochondrial Proton-Translocating ATPases; mitochondrie; lidé; zvířata; Genetic Predisposition to Disease; genetická predispozice k nemoci; mitochondriální protonové ATPasy